Pengaruh Promosi Online dan Harga Terhadap Keputusan Pembelian di Dhy Hijab Jombang - Ziniyatul Islamiyah (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to determine the effect of online promotions and prices, both privately and simultaneously on consumer purchasing decisions. This research is categorized as quantitative research using questionnaires as instruments. The population in this study were consumers who made purchases at the Dhy Hijab Jombang at the Jl. Bali No. 88 Jombang East Java. Samples taken as many as 30 respondents were determined by incidental sampling technique. The technique used is multiple regression. The results of this study indicate that : (1) Online promotion influences consumer purchasing decisions from t count = 8.049> t-table 1.967 and significance level 0.000. (2) The price has a positive effect on consumer purchasing decisions with a t-count value of 6.052 > t-table 1.967 and a significance level of 0.000. (3) Online promotions and prices simultaneously have a positive effect on consumer purchasing decisions with an F value of 36.404> F table value of 3.34 and a significance level of 0.000.